Health Promotion Strategies in Correctional Institution to Achieve Sustainable Development Goals (SDGs') - Satria, Hardiat Dani; Musthofa, Syamsulhuda Budi; Adi, Mateus Sakundarno (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Overcapacity in Correctional Institution (Lapas) is a prevailing issue faced by the Directorate General of Corrections (Ditjenpas). The current number of prisoners in correctional institution is nearly twice their ideal capacity, significantly impacting the health conditions of prisoners. Aims: To provide recommendations for health promotion strategies aimed at realizing healthy correctional institution in Indonesia, based on research conducted at Class IIA Kendal correctional institution. Method: This research is descriptive with a qualitative approach. Data collection methods comprised observation, interviews and documentation. Results: Achieving a healthy correctional institution requires a holistic approach through health promotion strategies encompassing several key aspects. Firstly, policy advocacy stands as the backbone in advocating for structural changes to improve healthcare access, adequate human resources and inclusive policies for prisoners. Furthermore, training prisoners and staff forms the foundation for improving healthcare services by providing necessary training, knowledge and support. Health education for prisoners serves as a long-term program to enhance their understanding of personal health and minimize disease risks. Lastly, enhancing personal hygiene behaviour is crucial in creating a clean environment, minimizing disease spread and supporting the overall health of both individuals and the correctional institution community. Conclusion: Realizing a healthy correctional institution through health promotion strategies is not solely a local effort but also a significant contribution towards achieving SDGs.